Factors Affecting Self-care Behaviors of Hypertension Patients in Mueang Chai Nat Municipality, Chai Nat Province - Kattinanon, Maytha; Poomputsa, Sermsup (Journal of Health Science of Thailand, 2018)
The purpose of this research was to study factors affecting self-care behaviors of hypertension patients in Mueang Chai Nat municipality. The samples were 222 hypertension patients in Mueang Chai Nat municipality who were treated at Chai Nat hospital. The instruments were questionnaires. Statistical tests used in the research were descriptive, reporting as percentage, mean, standard deviation; Pearsonีs product moment correlation coefficient and Stepwise multiple regression. The finding showed that the perceptions of hypertension patients in Mueang Chai Nat municipality about hypertension in general, perceived severity, perceived susceptibility with disease and perceived self ability to prevent complications were at high level. Perceive benefits of preventive and self-care behaviors and medical care instruction were at a moderate level. The patients received advice from family members, doctors, nurses and health personnel at high level. Most of self-care behaviors in patients were rated at a moderate level. There were positively significant relationships between perception about hypertension in general, susceptibility with disease and complications, severity, benefits, self ability to prevent complications, encouragement from people in family and advice from doctors, nurses and health personnel and self-care behaviors of hypertension patients in Mueang Chai Nat municipality, self ability to prevent complications and received advice from family members, doctors, nurses and health personnel were able to predict self care behaviors of hypertension patients in Mueang Chai Nat municipality at the level of 12.5 percent.